Task-Based Language Teaching As A Method of Instruction In Teaching Speaking - Mita Nur Aflah (Universitas Nahdlatul Ulama Blitar, 2021)
This paper aims to explore the theory on classroom instruction particularly Task-Based Language Teaching. It includes a short discussion of the definition and benefits of TBLT to help engaging students in a lesson by encouraging spoken interactions. In addition, teachers are encouraged to explore and experiment with TBLT in order to promote students active participation as well as to maximize opportunities for students to explore the target language. To strengthen the discussion, there is a guided framework to apply in the classroom as the subject matter for students to learn more effectively. Hopefully the paper could provide educators and instructors a method to use and to lead further studies for helping students to explore communicating in English. Moreover, this paper can also serve as a research reference in the field of classroom instruction, for instance in using TBLT to foster speaking skill.